2003
DOI: 10.1182/blood-2002-09-2889
|View full text |Cite
|
Sign up to set email alerts
|

Sex significantly influences transduction of murine liver by recombinant adeno-associated viral vectors through an androgen-dependent pathway

Abstract: A systematic evaluation of the influence of sex on transduction by recombinant adeno-associated viral vector (rAAV) indicated that transgene expression after liver-targeted delivery of vector particles was between 5-to 13-fold higher in male mice compared with female mice, irrespective of the proviral promoter or cDNA and mouse strain. Molecular analysis revealed that the rAAV genome was stably retained in male liver at levels that were 7-fold higher than those observed in females. Further, the sex difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
142
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(170 citation statements)
references
References 53 publications
25
142
3
Order By: Relevance
“…The underlying mechanisms for these female-specific phenomena are currently unknown. Davidoff et al 22 recently reported similar observations that AAV2-and AAV5-derived vectors less efficiently transduced livers of female mice than males. They suggested that the difference was due to an androgen-dependent pathway for augmenting hepatocyte transduction, but its mode of action is undetermined.…”
Section: Discussionmentioning
confidence: 64%
“…The underlying mechanisms for these female-specific phenomena are currently unknown. Davidoff et al 22 recently reported similar observations that AAV2-and AAV5-derived vectors less efficiently transduced livers of female mice than males. They suggested that the difference was due to an androgen-dependent pathway for augmenting hepatocyte transduction, but its mode of action is undetermined.…”
Section: Discussionmentioning
confidence: 64%
“…All of the vector-injected male mice from each cohort had liver tumors, but there was a relative delay in tumor formation in female mice, with 50%, 75%, and 100% of females developing tumors at 6 mo, 10 mo, and the time of being killed, respectively. The delay in females may have been due to decreased transduction (22) or hormonal effects on HCC development (23). The number of tumors increased with time, as did liver weight, also with a delay in females ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, liver transgene expression of rAAV vectors in males is five to 13-fold higher than in females, and this difference is mainly caused by androgens. 40 However, the detailed mechanism is unclear and other hepatic factors might also be involved since the difference occurred specifically in liver.…”
Section: Resultsmentioning
confidence: 99%